Psikologi Modern Perspektif Malik Badri (Analisis Kritis Atas Paradigma Psikoanalisa Dan Behaviourisme) - Arroisi, Jarman; Alfiansyah, Iqbal Maulana; Perdana, Martin Putra (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Abstract:Â MalikÂ Badri sees that concepts in Western psychology, especially in the flow of Behaviourism and psychoanalysis are very contradictory and problematic. Human beings and their souls, which are the main study of psychology, are mistakenly perceived by both schools, they assume that human beings are nothing but passive machines and filled with impulses of lust or libido. This is very contrary to the view of Islam,Â in fact, man is a creature whose fitrah is good and in addition to environmental factors, he is also influenced by internal factors in him such as feelings, beliefs, and so This research is library research where researchers take references from books, journals, and scientific papers figures. This research is urgent in order to prove the dangerous aspects of both schools of psychoanalysis and behaviorism. so that Muslim scholars, especially those engaged in Islamic psychology, are able to be selective in studying this flow.The results of this study are the conclusion that the flow of modern psychology, which in this context is psychoanalysis and behaviorism, is very dry about Islamic values because it is influenced by the philosophy of positivism, namely atheism and is also misguided in understanding human characteristics and chaotic in explaining the spiritual and religious processes of humans in Indonesia.